A cautionary note on the power of the test for the indirect effect in mediation analysis - Loeys, Tom; Moerkerke, Beatrijs; Vansteelandt, Stijn (Frontiers in Psychology, 2015)
Recent simulation studies have pointed to the higher power of the test for the mediated effect versus the test for the total effect, even in the presence of a direct effect. This has motivated applied researchers to investigate mediation in settings where there is no evidence of a total effect. In this paper we provide analytical insight into the circumstances under which higher power of the test for the mediated effect versus the test for the total effect can be expected in the absence of a direct effect. We argue that the acclaimed power gain is somewhat deceptive and comes with a big price. On the basis of the results, we recommend that when the primary interest lies in mediation only, a significant test for the total effect should not be used as a prerequisite for the test for the indirect effect. However, because the test for the indirect effect is vulnerable to bias when common causes of mediator and outcome are not measured or not accounted for, it should be evaluated in a sensitivity analysis.